2022
DOI: 10.3390/biomedicines10071686
|View full text |Cite
|
Sign up to set email alerts
|

Naringin and Naringenin: Their Mechanisms of Action and the Potential Anticancer Activities

Abstract: Naringin and naringenin are the main bioactive polyphenols in citrus fruits, the consumption of which is beneficial for human health and has been practiced since ancient times. Numerous studies have reported these substances’ antioxidant and antiandrogenic properties, as well as their ability to protect from inflammation and cancer, in various in vitro and in vivo experimental models in animals and humans. Naringin and naringenin can suppress cancer development in various body parts, alleviating the conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(72 citation statements)
references
References 101 publications
3
69
0
Order By: Relevance
“…For instance, quercetin was shown to have antioxidant, anti-inflammatory, antidiabetic, anti-Alzheimer’s, and anticancer activities [ 35 ] [ 36 ]. Moreover, in vitro and in vivo studies of the naringenin compound have claimed its strong association with the suppression of cancer progression [ 37 ]. Furthermore, a recent report also proved multiple activities of rutin toward inflammation, oxidation, and thrombosis [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, quercetin was shown to have antioxidant, anti-inflammatory, antidiabetic, anti-Alzheimer’s, and anticancer activities [ 35 ] [ 36 ]. Moreover, in vitro and in vivo studies of the naringenin compound have claimed its strong association with the suppression of cancer progression [ 37 ]. Furthermore, a recent report also proved multiple activities of rutin toward inflammation, oxidation, and thrombosis [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, ellagic acid is a tannin and has been reported to have antitumor properties [ 64 ]. Naringenin is a flavanone that has been reported to have antitumor properties [ 65 ]. Additionally, the flavonoid quercetin found in the leaves has been reported to have antitumor properties [ 38 ], and the isoflavone daidzein found in the stems has also been reported to have antitumor properties [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Naringenin is predominantly found in edible fruits such as Citrus species, tomatoes, and figs belonging to the Smyrna-type Ficus carica. Naringenin has the skeleton structure of a flavanone with three hydroxyl groups at the 4′, 5 and 7 carbons, a carbonyl group on the C ring, and a 5-OH group on the A ring, which are responsible for the antioxidant activity of naringenin [ 29 ].…”
Section: Flavonoids and The Mechanism Of Action Against High-grade Ad...mentioning
confidence: 99%
“…To date, numerous pre-clinical studies have suggested flavonoids as potential anti-cancer agents for high-grade adult-type diffuse gliomas [ 26 , 27 , 28 , 29 ]. However, a greater focus on flavonoids’ anti-high-grade adult-type diffuse glioma potential in targeting different molecules is needed to provide a more comprehensive understanding of its therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%